Synthesis of Isoxazolines and Isoxazoles via Metal-Free Desulfitative Cyclization - Cheng, Jiaxin; Yang, Ze; Li, Yuansheng; Xi, Yulan; Sun, Qiu; He, Ling (Synthesis, 2018)
A novel, one-pot reaction for the synthesis of isoxazolines and isoxazoles is developed via a cascade process under metal-free conditions. The approach involves the formation of intramolecular C–N and C–O bonds and intermolecular C–C bonds from aromatic alkenes or alkynes and N-hydroxysulfonamides using hypervalent iodine(VII) and iodine as the oxidant. Activation of C–H and C–C bonds/construction of C–O bonds/elimination of SO2/C–N bond formation is achieved in sequence in the reaction system.
Keywords: isoxazolines; isoxazoles; desulfurization; radical cyclization; tandem reaction